Can timber provision from Amazonian production forests be sustainable?. (13th June 2019) - Piponiot, Camille; Rödig, Edna; Putz, Francis E; Rutishauser, Ervan; Sist, Plinio; Ascarrunz, Nataly; Blanc, Lilian; Derroire, Géraldine; Descroix, Laurent; Guedes, Marcelino Carneiro; Coronado, Euridice Honorio; Huth, Andreas; et al.
Abstract: Around 30 Mm 3 of sawlogs are extracted annually by selective logging of natural production forests in Amazonia, Earth's most extensive tropical forest. Decisions concerning the management of these production forests will be of major importance for Amazonian forests' fate. To date, no regional assessment of selective logging sustainability supports decision-making. Based on data from 3500 ha of forest inventory plots, our modelling results show that the average periodic harvests of 20 m 3 ha −1 will not recover by the end of a standard 30 year cutting cycle. Timber recovery within a cutting cycle is enhanced by commercial acceptance of more species and with the adoption of longer cutting cycles and lower logging intensities. Recovery rates are faster in Western Amazonia than on the Guiana Shield. Our simulations suggest that regardless of cutting cycle duration and logging intensities, selectively logged forests are unlikely to meet timber demands over the long term as timber stocks are predicted to steadily decline. There is thus an urgent need to develop an integrated forest resource management policy that combines active management of production forests with the restoration of degraded and secondary forests for timber production. Without better management, reduced timber harvests and continued timber production declines are unavoidable.